Resource sharing and networking among the libraries of the Ministry of Human Settlements and attached agencies - Lucas, Zenaida F.; Hidalgo, Namnama P.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
This study looked into the resources and state of resource sharing with implications for networking among the libraries of the Ministry of Human Settlements and 17 attached agencies. It describes their information resources, services, budget, equipment, manpower and clientele as well as their attitudes toward the establishment of a human settlements information network.
A structured questionnaire used to collect data for the study was sent to the MHS Library and the libraries of the 28 MHS attached agencies on March-June 1985. Only 18 libraries responded including the MHS Library. Interviews and phone calls supplemented the answers of the respondents.
The biggest book collection is that of the Cultural Center of the Philippines with 6751 books and the smallest book collection is National Pollution Control Commission with 110 books. Only Intramuros Administration, Cultural Center of the Philippines, Technology Resource Center, Philippine Heart Center for Asia and National Commission on the Role of Filipino Women have print and non-print materials. The median collection size is 795. The collection of the libraries are on the 11 basic needs of man; i.e. water, power, food, clothing, shelter, economic base, medical services, education and culture and technology, ecological balance, sports and recreation and mobility. Agencies with distinctive functions like the CCP and the Intramuros Administration collect materials in humanities and culture and on the restoration and historical materials relevant to Intramuros.
Only three libraries appear to have planned collection development. These are Technology Resource Center, Home Development Mutual Fund and Human Settlements Regulatory Commission.The libraries have organized collections. The Dewey Decimal Classification Scheme is used by 44.5 percent of the libraries while the Library of Congress Classification Scheme is used by 29 percent of the libraries. OHCA uses the National Library of Medicine Classification while the MHS and HSDC have devised their own classification systems. The collections are inadequate due to 1) lack of funds in 50 percent of the libraries, 2) lack of materials in 16.66 percent of the respondent libraries and 3) lack of staff as cited by one respondent.
On the manpower aspect, the NCRFW and National Parks has eight library staff and MHS seven staff members. Six libraries are manned by only one staff member each. Eighteen librarians have professional/educational training in library science, while some are degree holders in education, political science, biological science, etc. Other staff members are secretarial graduates. Services to clientele include browsing, referral, current awareness and accessions lists. Fifteen libraries allow outsiders to use their resources, while three libraries do not do so because of 1) organizational policy, 2) budget constraints and 3) lack of room for outsiders. Interlibrary lending is the most common form of cooperative activity, followed by photocopying of materials and exchange of publications. The libraries expressed the need to acquire equipment such as 1) computer, 2) card catalog duplicator and 3) photos duplicating machines. Such equipment will facilitate information networking and resource sharing among the libraries.
Thirteen libraries or 61 percent of the respondents are interested in joining an MHS information network as against four libraries or 38 percent of the respondents not in favor of networking. Those against networking cited the following reasons: 1) lack of funds, 2) lack of staff, 3) their collections are too small to share with other libraries, 4) administrative difficulty, 5) no one has initiated a networking project and 6) lack of need.
The benefits to be derived from networking as perceived by those in favor are necessary for success: 1) sharing of resources, 2) willingness to modify policies, 3) willingness to work with the administrator, 4) willingness to pay for incidental expenses, and 5) willingness to participate in fundraising activities.
The Ministry of Human Settlements Library cited by most of the respondents as the most likely focal point of networking because of its funding availability, manpower complement and the MHS being the mother agency which would facilitate the coordination of resource sharing and networking among the attached agencies. The establishment of a human settlements information network is recommended, with specific attention to housing information.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library cooperation -- Philippines; Library information networks -- Philippines